Subsitution Of Tempe Flour In Rice Flour On Protein Levels and Organoleptic Quality Of Jaje Laklak - Indra Dewi, Kadek Ayu Cahyani; Sri Sugiani, Pande Putu; Tamam, Badrut (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Jaje laklak is one of the traditional Balinese snacks. Generally, jaje laklak is made from rice flour, which is served with additional grated coconut on top and given additional liquid brown sugar on top of the jaje laklak. The purpose of this study was to determine how the effect of substitution of tempeh flour on organoleptic quality and nutritional value, this type of experimental research used a randomized block design (RAK) with 5 treatments, namely P1 (10% tempeh flour substitution), P2 15% tempeh flour substitution, P3 (20% tempe flour substitution), P4 25% tempe flour substitution, P5 30% tempe flour substitution. The data were analyzed using the ANOVA test followed by the BNT test. The subjective analysis results of jaje laklak included color, aroma, texture, taste, acceptance overall, color quality, aroma quality and texture quality are significant. The results of objective analysis are protein content. The best protein content results in jaje laklak is 9.85 grams. The lowest protein content results are P2 of 6.81 grams with categories like and protein content the highest was P5 of 9.85 grams with the least preferred category by the panelists.The results of the organoleptic quality analysis for the highest level of preference were jaje laklak the first treatment a with substitution of 10 grams of tempeh flour and 90 grams of rice flour.